2003
DOI: 10.1152/ajpheart.00119.2003
|View full text |Cite
|
Sign up to set email alerts
|

Biventricular mechanical asynchrony predicts hemodynamic effect of uni- and biventricular pacing

Abstract: We tested whether biventricular resynchronization explains contractile function changes with univentricular and biventricular pacing in heart failure patients with varying magnitudes of baseline biventricular asynchrony. Thirty patients (New York Hospital Association class > or = III, QRS duration > or =120 ms) were tested. Contractile function was measured by left ventricular maximum first derivative of pressure over time (dP/dtmax). Biventricular mechanical asynchrony was quantified by the normalized pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 28 publications
3
36
0
1
Order By: Relevance
“…49 Although these effects have been demonstrated most clearly during RVA pacing, biventricular or LV pacing may also induce dyssynchrony in hearts with normal ventricular conduction 504 and can reduce LV systolic function in patients with no baseline dyssynchrony. 505 In patients with no AV block and no intraventricular conduction abnormalities, ventricular pacing should be avoided as much as possible. For many ICD patients who do not have an indication for bradycardia support, this can be achieved by programming a very low backup ventricular pacing rate (i.e., 30 to 40 bpm).…”
Section: Selection Of Implantable Cardioverterdefibrillator Generatorsmentioning
confidence: 99%
“…49 Although these effects have been demonstrated most clearly during RVA pacing, biventricular or LV pacing may also induce dyssynchrony in hearts with normal ventricular conduction 504 and can reduce LV systolic function in patients with no baseline dyssynchrony. 505 In patients with no AV block and no intraventricular conduction abnormalities, ventricular pacing should be avoided as much as possible. For many ICD patients who do not have an indication for bradycardia support, this can be achieved by programming a very low backup ventricular pacing rate (i.e., 30 to 40 bpm).…”
Section: Selection Of Implantable Cardioverterdefibrillator Generatorsmentioning
confidence: 99%
“…4,5,9 The mechanisms by which LV-only pacing works remain somewhat controversial. 10 Fusion with electrical activity from the AV node is a possibility [11][12][13] ; however, experimental data have suggested that electrical synchrony is not a prerequisite for mechanical synchrony. 14 Another possible explanation is that early activation of the lateral wall is preferable to the septum, ie, that dyssynchrony associated with right bundle-branch block-type delay is less than that associated with left bundle-branch block-type delay.…”
Section: Discussionmentioning
confidence: 99%
“…11 As for the latter, several recent reports have suggested that selection based on the direct assessment of mechanical dyssynchrony by tissue-Doppler echocardiography is a potentially useful tool to increase response rate for CRT. [12][13][14][15][16][17] As for the optimal LV pacing site, the PATH-CHF II study has demonstrated that pacing at LV free wall sites consistently produces better short-term hemodynamic responses than does pacing at LV anterior sites. 4,5 Furthermore, Auricchio et al demonstrated that the functional block line of LV, as determined by CARTO and non-contact mapping, varied among individual patients with left bundle branch block (LBBB) (ie, anterior, lateral, or inferior aspects), and suggested that the site of delay above the functional block line was the optimal pacing site.…”
Section: Discussionmentioning
confidence: 99%